Understanding Student Loan Decisions: A Literature Review. (March 2015) - Cho, Soo Hyun; Xu, Yilan; Kiss, D. Elizabeth
<x xml:space="preserve">Abstract</x> Because of the continuing increase in college costs and the need for a college education, the use of student loans has affected many individuals and households in the United States. Researchers and policy‐makers need a comprehensive review of literature to understand the determinants and consequences of student loans. This article provides information on the current trends in student loans, reviews the effect of education loans on college enrollment and career decisions, as well as the effects on personal life decisions. Implications for future research related to methodology, information, and the decision‐making process for an at‐risk population are offered.